(untitled) (Journal of Human Sciences, 2025)
The study investigates how the mother tongue influences second language learning, focusing on students at the Faculty of Arts and Science in Zamzam. It examines the impact of native language on acquiring English, considering factors like input, motivation, and learning strategies. Through a mixed-method approach, data from English department students were analyzed, revealing a significant effect of the mother tongue on learning English. Key findings include challenges in mastering core language skills—reading, speaking, listening, and writing—due to reliance on the native language. The study underscores the importance of strategies that minimize mother tongue interference, suggesting practices such as fostering thinking in the target language, interactive classrooms, and extensive reading to improve language acquisition outcomes. These insights aim to enhance pedagogical approaches, ensuring effective language learning by addressing the specific needs arising from native language influences..